Improvement of Experimental Equipment Based on the One-Step Outflow Test and Research on Rapid Determining SWCC - Jiaqi Wu; Huan Li; Anming Wang; Zhiquan Huang (Advances in Civil Engineering)
The soil-water characteristic curve (SWCC) is an important hydraulic parameter for modeling water flow and contaminant transport in the unsaturated soil. However, direct measurement of the SWCC is still difficult. The commonly used measuring instrument in the laboratory is the pressure plate extractor. In this paper, the original pressure plate extractor has been improved based on the one-step outflow test. Compared with the original pressure plate extractor, three devices, water storage, data acquisition system, and bubbles scouring device, are added to the improved pressure plate extractor. The improved equipment eliminates the problems of long test time consumption and inaccurate test data. A one-step outflow test is performed utilizing the improved pressure plate extractor. The test data (the amount of spilled water and the time of pressurization) are substituted into the one-dimensional moisture migration analysis software HYDRUS-1D. The parameters (α, m, and n) are identified by the numerical inversion method in the inversion module of the HYDRUS-1D, which are associated with the VG model to fit SWCC. The fitted SWCC is highly consistent with the measured SWCC, which is obtained from the conventional test of the original pressure plate extractor. Results confirm that the improved pressure plate extractor not only saves considerable time but also effectively measures the SWCC. The improved pressure plate extractor also involves a simple operation. The influence factors of controlling the geometry of SWCC are also discussed, the results of the discussion confirm that the geometry of SWCC is directly controlled by pore distribution, and the consolidation pressure is an indirect factor.